JUAL BELI DENGAN MENGGUNAKAN SISTEM DROPSHIPPING DALAM PERSPEKTIF EKONOMI ISLAM - Alfi Amalia (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2023)
Buying and selling is a legalized transcend in Islam. However, the implementation must be in accordance with the rules applicable in sharia. So that the realization of good and perfect sale and purchase transactions in accordance with the teachings of Islam. With the technological sophistication of today, causing a shift in the system of buying and selling in the community, one of which is not require that the seller owns and knows the state of the goods to be sold. The sale and purchase system is called dropshipping system. This research uses literature study approach using qualitative descriptive method. The results of this study indicate that the transaction dropshipping model after reviewing from the side of harmonious and the terms of sale and purchase of Islam, has met the pillars of the contract in sharia. While On the ownership of goods in the practice of selling and selling dropshipping has two opinions, namely: 1. Prohibited, that the goods have not been fully owned by the seller because the goods are still in the hands of the owner (supplier). 2. It is permitted, even though the seller has no stock of goods to sell, provided the seller obtains the consent of the owner of the goods and may hold or present the goods to be traded, as the seller in the dropshipping model transaction is principally a representative for the owner